2022
DOI: 10.1098/rsif.2021.0805
|View full text |Cite
|
Sign up to set email alerts
|

No apparent effect of a magnetic pulse on free-flight behaviour in northern wheatears ( Oenanthe oenanthe ) at a stopover site

Abstract: Naïve migrants reach their wintering grounds following a clock-and-compass strategy. During these inaugural migrations, birds internalise, among others, cues from the Earth's magnetic field to create a geomagnetic map, with which they navigate to destinations familiar to them on subsequent migrations. Geomagnetic map cues are thought to be sensed by a magnetic-particle-based receptor, which can be specifically affected by a magnetic pulse. Indeed, the orientation of experienced but not naïve birds was compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 76 publications
2
25
6
Order By: Relevance
“…Therefore, it is not obvious why such landmarks would be more important at our test site than at others. It remains unclear why free-flying birds in Holland (2010) and Holland and Helm (2013) responded to the magnetic pulse with a deflected departure direction, but not in our present study or in Karwinkel et al (2022).…”
Section: Is Geomagnetic Map Information Dispensable For Migratory Birds?contrasting
confidence: 64%
See 4 more Smart Citations
“…Therefore, it is not obvious why such landmarks would be more important at our test site than at others. It remains unclear why free-flying birds in Holland (2010) and Holland and Helm (2013) responded to the magnetic pulse with a deflected departure direction, but not in our present study or in Karwinkel et al (2022).…”
Section: Is Geomagnetic Map Information Dispensable For Migratory Birds?contrasting
confidence: 64%
“…We consequently expanded our study to further explore the role of distance to final destination on magnetic map navigation and repeated our pulsing study with the same methodology on a short to medium distance migrant, the European robin ( Erithacus rubecula , hereafter robin). During spring stopover on Helgoland, robins are much closer to their migratory destination [some 50 to 1250 km], in this case to their breeding sites (Dierschke et al 2011), compared to wheatears in our former study, whose destination was their African wintering grounds (Karwinkel et al 2022). Importantly, in an independently conducted study, free-flying robins have been reported to be affected by magnetic pulse pre-treatment on spring migration (Holland 2010).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations